Physics ContributionsQuality assurance procedures during commissioning of a treatment planning system as a tool to establish new standards before migration - Bielęda, Grzegorz; Zwierzchowski, Grzegorz; Błasiak, Barbara; Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2010)
Purpose: Treatment planning system commissioning is one of the most important parts of the quality assurance system in a working brachytherapy department. Migration to a more sophisticated system is always a step forward for the planning team but careful verification of the workflow and obtained results is mandatory. The question is not only whether the quality and safety of the previous standards can be preserved, but also about the possibility of reaching a higher level. The general objective of this study was to compare and verify calculation algorithms implemented in the treatment planning systems Plato Brachytherapy v.14.3.7 and Oncentra Masterplan (Brachy) V.3.1 SP 3. Material and methods: In order to revise the optimization algorithms implemented in the compared treatment systems, a series of 20 interstitial breast cancer applications were used. Treatment plans were optimized using geometric optimization with distance option. The parameters V, D90, D100, V100, V150, V200 and DNR were gained for target volume. On the basis of the value of Student’s t-test parameters ( = 0.05) plans prepared using optimization algorithms implemented in the two treatment planning systems were compared. Results: For the treatment plans prepared using Oncentra Masterplan a lower value of DNR (p = 0.018) was obtained. Uniformity of the dose distribution does not collide with comparable D90 values for both treatment planning systems (p = 0.109). Dose throughout the target volume (D100) was also proved to be higher in plans prepared using Oncentra Masterplan (p = 0.012). Conclusions: For interstitial applications Oncentra Masterplan planning system enables one to prepare a more homogeneous dose distribution but also a higher dose in the whole treated volume, while the volume covered with the therapeutic dose does not statistically differ.